2021
DOI: 10.1002/wer.1492
|View full text |Cite
|
Sign up to set email alerts
|

Primary sludge fermentate as carbon source for mainstream partial denitrification–anammox (PdNA)

Abstract: Primary sludge fermentate, a concentrated hydrolyzed wastewater carbon, was evaluated for use as an alternative carbon source for mainstream partial denitrificationanammox (PdNA) in a suspended growth activated sludge process in terms of partial denitrification (PdN) efficiency, PdNA nitrogen removal contributions, and final effluent quality. Fermenter operation at a 2-day sludge retention time (SRT) resulted in the maximum achievable yield of 0.14 ± 0.05 g sCOD/g VSS without release of excessive ammonia and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
1
34
1
Order By: Relevance
“…Overall, this study showed that the main mechanism for PdN selection remains the management of nitrate residual as suggested before by Le et al (2019b), and when low quality fermentate is used an elevated nitrate setpoint will be needed to enhance PdN selection. It was also hypothesized that increased nitrate residuals during phase 1 might allow for increased PdN selection, and PdN efficiencies closer to previously reported numbers (Ali et al, 2021). In addition, optimization of ABAC setpoints is crucial to maximize PdNA rates by providing the right NH 4 + ‐N/NO 3 − ‐N stoichiometry.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Overall, this study showed that the main mechanism for PdN selection remains the management of nitrate residual as suggested before by Le et al (2019b), and when low quality fermentate is used an elevated nitrate setpoint will be needed to enhance PdN selection. It was also hypothesized that increased nitrate residuals during phase 1 might allow for increased PdN selection, and PdN efficiencies closer to previously reported numbers (Ali et al, 2021). In addition, optimization of ABAC setpoints is crucial to maximize PdNA rates by providing the right NH 4 + ‐N/NO 3 − ‐N stoichiometry.…”
Section: Resultssupporting
confidence: 82%
“…As expected, PdN efficiency was lower than those associated with acetate, glycerol, and methanol (Campolong et al, 2019; Fofana, Bachmann, et al, 2021; Fofana, Chen, et al, 2021; Le et al, 2019a, 2019b). Much more intriguing is that this study's highest PdN efficiency was also lower than that observed using primary sludge fermentate in suspended post‐anoxic PdNA configuration (49%) by Ali et al (2021). Unlike suspended configuration, the addition of biofilm carrier media in an IFAS implementation enabled biomass to grow in conjunction as activated sludge and biofilm, and provided a way to increase capacity in reactors.…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations